Recreational drug use among young, hospitalized patients with acute coronary syndrome: A retrospective study - Femke M.J. Gresnigt; Meike Hulshof; Eric J.F. Franssen; Joost W. Vanhommerig; Dylan W. de Lange; Robert K. Riezebos (Toxicology Reports, 2022)
Background: Cocaine use is a well-established risk factor for acute coronary syndrome (ACS) although other recreational drugs (RD), are increasingly considered as potential cardiac risk factors. Compared to ACS without RD use, worse outcomes have been described for RD-associated ACS. Objective: The aim of this study was to explore the use of RD in a contemporary cohort of young ACS patients. Methods: Between June 2016 and October 2019, ACS patients aged 18–50 years, admitted to OLVG Hospital in Amsterdam, were retrospectively analysed. Medical chart review was performed to obtain patient and clinical characteristics, RD use, cardiac risk factors, outcome and follow up. Results: A total of 229 patients were included in the study. Recreational drug use prior to ACS was present in 24.9% of all patients, with cannabis (16.2%), cocaine (4.8%), or both (2.6%) most commonly observed. RD users were predominantly young men (87.7%) and had a significantly higher tobacco use compared to non-RD users (89.5% vs. 62.8%, P < 0.001), also after adjusting for age and sex. RD use was associated with larger myocardial infarctions with significantly higher CK-MB levels (104 ± 116 U/L vs 62 ± 96, P = 0.040) and poorer left ventricular function measured by echocardiography as compared to non-users (P = 0.007). Conclusion: Recreational drug use was present in almost 25% of all young ACS patients evaluated for drug use and was associated with larger myocardial infarction resulting in poorer left ventricular function as compared to non-users. Additionally, RD-users were younger and were more often tobacco users, compared to non-users.